Ipomoea aquatica Forssk as potential phenol phytoremediator - Lee, Siew Yi (2015)
Despite widespread applications of phenol in industries such as pesticides and oil refineries, leaking of phenol into aquatic environment remained a common issue. It causes water pollution and can lead to acute and chronic damages to plants, animals and human upon contact or consumption. There are many technologies currently practised to remediate phenol pollution. For examples, soil removal, chemical treatments and biological degradation using fungi. However, each of the current technology has some limitations and weakness. Hence, phytoremediation was proposed to be an alternative phenol remediator. In the present study, Ipomoea aquatica Forssk (water spinach) was treated with different concentration of phenol to test its ability to biodegrade phenol. I. aquatica Forssk was chosen for this project because it is highly tolerant to pollutants, cheap and fast growing. The plants were grown in containers with 4 Litre of phenol spiked water for duration of 14 days. Data such as length of plant structures and remaining phenol concentrations were taken every day. Remaining phenol concentrations were assayed using 4-Aminoantipyrine (4-AAP) method. Then, all data were analysed statistically. In 0.10 g/L phenol, I. aquatica Forssk was least damaged with induced roots growth. Results also show that I. aquatica Forssk is capable of survive and biodegrades phenol up to 0.30 g/L despites morphological damages such as scars on stems, nodal root growth inhibition and yellowish leaves. Phenol concentration higher than 0.30 g/L will be fatal to the I. aquatica Forssk. Highest rate of phenol degradation was 0.021 g/L per day upon exposure to 0.30 g/L phenol.